H5J (Hypnotic 5 Fingers) Mobile Application For Reduce Anxiety Problems Chemotheraphy Patient - Eky Madyaning Nastiti; Ahmad Guntur Alfianto; Feri Ekaprasetia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: Chemotherapy as a therapy for cancer patients has several effects, one of which is anxiety. Anxiety can be reduced by using relaxation techniques. One of these relaxation techniques can be done with five finger hypnosis. These efforts can be modified in accordance with the 4.0 industrial revolution by using digital technology. Objective: The purpose of this study was to develop H5J (Mobile Application Hypnotic 5 Fingers) to reduce anxiety problems in chemotherapy patients. Methods: The application was developed through two stages, the first was carried out by creating application content and sophisticated systems by technology experts. Furthermore, in the second stage, a perception test was performed in the fields of mental, medical surgical nursing and information technology expert. Then, 100 patients with chemotherapy were assessed in Jember Regency Malang Regency, East Java, Indonesia using a learning media questionnaire, and Intraclass Correlation Coefficients (ICC) test. The H5J Mobile application contains menu content that provides information about non-pharmacological relaxation therapy material relaxation distraction in the form of five-finger hypnosis (hypnosis guide and five-finger hypnosis wave) in industrial era 4.0. Results: The statistical analysis showed the value of 0.875, while the average of 3 assessors was 0.964> 0.5 (high stability). Furthermore, from the diligence results, 86.78% of the patients stated that the application was very suitable for use, while 13.22% commented that it was feasible. Conclusion: H5J Mobile Application was a health application used for chemotherapy patients and was able to reduce anxiety.